Does affirmative action address ethnic inequality? A systematic review of the literature - Simone Schotte; Rachel M. Gisselquist; Tharcisio Leone (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Despite the good intentions behind affirmative action (AA) policies to mediate 'horizontal inequalities' between ethnic groups, the evidence on their effectiveness remains open to debate. In this study, we conduct a systematic review of the literature with global scope, to add new clarity on whether positive or negative effects prevail according to the available quantitative evidence and the strength and generalizability of this evidence. Overall, close to two-thirds of the 194 reviewed studies find a dominantly positive effect. However, three limiting factors condition this aggregate assessment. First, while AA generally improves the numerical representation of target groups, the qualitative implications of these policies are more ambiguous. Second, the concentration of the evidence on a limited set of country cases may distort our perception of the effectiveness of AA. Third, causal evidence on the impact of AA is generally scarce and studies applying quasi-experimental research methods generally arrive at a more positive assessment than studies applying less rigorous methods.
Keywords: I38; J15; 330; affirmative action; systematic review; horizontal inequalities; ethnic groups